Productivity and economics of mixed intercropping of potato with other short duration vegetables (Bangladesh Agronomy Journal, 2015)
Mixed cropping has proven to be a useful approach to maximizing the crop productivity. Now a day, poverty alleviation of resource poor farmers is an important issue in Bangladesh and hence, mixed cropping system can be helpful to food security as well as to reduce poverty. The experiment was carried out at Moulvibazar and Sylhet districts during 2011-12 and 2012-13 to find out the agronomic performance of mixed intercropping of potato with different short duration vegetables crop and to increase the cropping intensity and profitability of the farmers in Sylhet region. The trial was conducted following RCB design with six dispersed replications. There were five treatments: T1: sole potato (100%), T2: potato (100%) + bush bean (50%), T3: potato (100%) + garden pea (50%), T4: potato (100%) + radish (50%) and T5: potato (100%) + bush bean (25%) + garden pea (15%) + radish (10%) used in the trial. Results revealed that the highest equivalent yields of potato 37.09 and 35.37 t ha-1 were recorded in potato (100%) + radish (50%) mixed intercropping system from Moulvibazar and Sylhet, respectively. Cost benefit analysis also  showed that  highest gross returns Tk. 3,70,910 and 3,53,690 and net returns Tk. 2,65,710 and 2,48,490 and benefic benefit cost ratio 3.53 and 3.36 were recorded in the same treatment combination in both locations, respectively. So, 100% potato with 50% radish intercropping system may be recommended as profitable mixed intercropping system in Sylhet region.Bangladesh Agron. J. 2014, 17(2): 39-46